METHODOLOGICAL BASIS MATRIX DIAGNOSTICS OF RISKS OF THE ENTERPRISE - A. M. Medvedeva (Модернизация, инновация, развитие, 2016)
Risk management is part of the enterprise management process and more precisely, of all its constituent elements: processes, resources, technology, etc. Specific for the management of these elements is that it is aimed at minimization of undesirable effects of possible events whose occurrence may worsen enterprise performance actual results as against those expected (planned).